Representation of Georgette Vallejo in Peruvian dramaturgy - Yangali Vargas, Jorge (2023)
In this article, we review three plays that have Georgette Vallejo as a character. In the last years of the present century, the life and work of César Vallejo’s wife has been the object of analysis and representations by different scriptwriters and directors, who coincide in one point: the vindication of Georgette Vallejo in the face of the vituperation she received during her lifetime.